CCL3 as a novel biomarker in the diagnosis of necrotizing enterocolitis - Li Zeng; Wei Liu; Yue Li; Zhixin Song; Hongdong Li; Yibing Yin; Dapeng Chen; Xi Yuan (BMC Pediatrics)
Abstract Objectives Neonatal necrotizing enterocolitis (NEC) is a common intestinal disease that threatens the lives of newborns and is characterized by ischemic necrosis of the small intestine and colon. As early diagnosis of NEC improves prognosis, the identification of new or complementary biomarkers is of great importance. In this study, we evaluate the diagnostic value of CCL3 in NEC and compare its effectiveness with other commonly used biomarkers, such as procalcitonin (PCT) and C-reactive protein (CRP). Participants and design Serum samples were collected from 64 patients with NEC and 38 jaundice neonatal controls. Before initiating therapy, blood samples for the whole blood count, CRP, PCT and CCL3 were obtained from all neonates. Receiver operating characteristic (ROC) curve and multivariate logistic regression analyses were performed. Setting Department of Clinical Laboratory, Children’s Hospital of Chongqing Medical University. Results The serum CCL3 level of the NEC group was significantly higher than that of the Control group. The ROC area under the curve (AUC) was 0.8614 (95%confidence interval (CI) 0.7863–0.936; p < 0.0001) for CCL3, 0.8534 (95% CI 0.7682–0.9386; p < 0.0001) for PCT, 0.675 (95% CI 0.5625–0.788; p < 0.0001) for CRP, 0.579 (95% CI 0.4402–0.7188 p = 0.2460) for WBC, and 0.7384 (95% CI 0.6215–0.8554 p = 0.0005) for PLT. With a cut-off value of 83.33 ng/ml, the diagnostic sensitivity and negative predictive value of CCL3 were 83.33% and 80.55%, respectively. The combined use of CCL3 and PCT could significantly improve diagnostic performance for NEC (0.903; 95% CI 0.810–0.960; p < 0.0001). Conclusions CCL3 may be used as a promising biomarker for the diagnosis of NEC, and the combined use of CCL3 and PCT could improve the diagnosis of NEC.